Dramatic Structure in Teuku Umar Theater Show in Meulaboh City, West Aceh Regency - Radhiah, Aisyatur; Jazuli, Muhammad; Wadyio, Wadyio (Universitas Negeri Semarang, 2019)
Mappadendang traditional ceremony is a traditional ceremony that is held every year by Bugis society as an expression of gratitude for the abundance of the results of the crop. This traditional ceremony is usually combined with the Padendang dance, which is a traditional dance of the Bugis people, especially in Abbanuangnge Village, Soppeng Regency. It is derived from the word